MUDAWWANA REFORMATION (A Study of the Literature of Religious Courts in Morocco) - Farid Afif Syahputra Rinaldi (Universitas Islam Negeri Sumatera Utara, 2022)
The existence of religious courts in Morocco experienced various problems, ranging from the application of Islamic law, to the codification process that was used as a reference in the implementation of justice. Morocco's legal system is heavily influenced by the legal system implemented by France and Spain. However, family law (al-Ahwal al-Syakhshiyyah), which is based on Islamic law, is still upheld by Muslims in Morocco based on the Maliki school of thought and its judicial body known as the Sharia Court The type of judiciary in the Moroccan State consists of the Court of Cassation, the Constitutional Court, the Supreme Council of Judicial Power and the Moroccan Hebrew Judiciary In 1965, within a decade after the codification of Mudawwana, an official commission was formed to find solutions to deficiencies in family law, such as on guardianship and maintenance of marriage. After the first meeting, however, nothing more was heard from this commission. Parliament reformed the family law again in 1970, 1974, and in 1979. The formulation of the problem in this article is How was the Religious Courts in Morocco before independence? How is the Religious Courts in Morocco after independence? What is the position of Islam in the legal system in Morocco? What are the types of courts in Morocco? How is the reform process (Mudawana) of Moroccan family law? The purpose of writing this paper is to find out how the Religious Courts in Morocco before independence, Religious Courts in Morocco after independence, The position of Islam in the legal system in Morocco, Types of Courts in Morocco and the process of reform (Mudawana) Moroccan family law.Keywords:Morocco,Mudawwana,ReligiousCourts